Activating the somatosensory system enhances net quadriceps moment during gait. (3rd January 2019) - Fischer, Arielle G.; Erhart-Hledik, Jennifer C.; Asay, Jessica L.; Chu, Constance R.; Andriacchi, Thomas P.
Abstract: Quadriceps muscle rehabilitation following knee injury or disease is often hampered by pain, proprioception deficits or instability associated with inhibition of quadriceps activation during walking. The cross-modal plasticity of the somatosensory system with common sensory pathways including pain, pressure and vibration offers a novel opportunity to enhance quadriceps function during walking. This study explores the effectiveness of an active knee brace that used intermittent cutaneous vibration during walking to enhance the peak knee flexion moment (KFM) during early stance phase as a surrogate for net quadriceps moment (balance between knee extensor and flexor muscle moments). The stimulus was turned on prior to heel strike and turned off at mid-stance of the gait cycle. Twenty-one subjects with knee pathologies known to inhibit quadriceps function were tested walking under three conditions: control (no brace), a passive brace, and an active brace. Findings show that compared to the control, subjects wearing an active brace during gait exhibited a significant (p < 0.001) increase in peak KFM and no significant difference when wearing a passive brace (p = 0.17). Furthermore, subjects with low KFM and knee flexion angle (KFA) in control exhibited the greatest increase in KFA at loading response in the active brace condition (R = 0.47, p < 0.05). Intermittent cutaneous stimulation during gait, therefore, provides an efficient method for increasing the KFM in patients with knee pathologies. This study's results suggest that intermittent vibration stimulus can activate the cross-modalities of the somatosensory system in a manner that gates pain stimulus and possibly restores quadriceps function in patients with knee pain.